Overview at modern mine detecting robots - Karpenko, A. (ХНУРЕ, 2024)
In this article, main robotic solutions for mine detection and demining were reviewed using such criterias, as approaches to detection and demining, types of utility tools and mechanical parts. As result, the general view at types of mine detecting robots and distribution of their use case amounts was gathered
Keywords: BOZENA; explosives; GPR; demining; robot